New calculation method to solve moisture balance in the room with regenerator heat recovery and infiltration. (October 2017) - Pomianowski, Michal; Heisleberg, Per; Drivsholm, Christian
Abstract: This paper investigates moisture related performance of a regenerator heat exchanger located in a decentralized ventilation unit for residential building application. The decentralized ventilation solutions have recently become a more and more popular alternative to centralized ventilation systems. Due to the small space available and in order to avoid maintenance of these types of units, they are equipped with regenerator heat exchanger in some cases. In the recent past and also presently, Building Regulations (BR) and European directives have increased demands for heat recovery efficiency in air handling units (AHUs). In the case of regenerator heat exchanger, the higher the heat recovery efficiency obtained the higher risk that condensation might occur. This condensation might form small droplets on the surface of the regenerator that might not be possible to drain in the short switching time of the regenerator and consequently might be evaporated in the next cycle back to the building and cause elevated humidity conditions in the indoor spaces. Due to the fact that the traditionally used dilution equation must not be used to solve moisture balance in the room with regenerator heat exchanger and infiltration, this paper presents a new calculation methodology that takes into account infiltration, condensation in the regenerator, and back evaporation to the room. The paper compares humidity levels in the room ventilated with regenerator heat exchanger and ordinary counter-flow exchanger. Theoretical calculations indicate that the ability of a ventilation system with regenerator to remove moisture from the room is very dependent on moisture loads in the room, air change rate, and infiltration rate.